Monosubstitution of 1H‐Imidazo[4, 5‐f][1, 10]phenanthroline Ligands Yields Maximum Luminescence Quantum Yield in Ruthenium Polypyridyl Complexes. Issue 7 (2nd May 2022) - Lämmle, Martin; Bagemihl, Benedikt; Nauroozi, Djawed; Petermann, Lydia; Pannwitz, Andrea; Rau, Sven
Abstract: Six different monoarylated N‐aryl‐1 H ‐imidazo[4, 5‐ f ][1, 10]phenanthroline (Rip) ligands and their corresponding ruthenium complexes [(tbbpy)2 Ru(Rip)] 2+ Ru(Rip) have been synthesized bearing different aryl substituents on the imidazole unit including electron donating and accepting groups. N, N'‐disubstitution on the imidazole unit yielded five new 1‐aryl‐3‐benzyl‐1 H ‐imidazo[4, 5‐ f ][1, 10]phenanthrolinium bromide (RR'ip) + ligands and the corresponding ruthenium complexes [(tbbpy)2 Ru(RR'ip)] 3+ Ru(RR'ip). All complexes were characterized in terms of their structural, photophysical, photochemical and electrochemical properties. The photophysical data revealed a high luminescence quantum yield (21.6–22.8 %) for monoarylated Ru(Rip) complexes compared to [Ru(bpy)3 ] 2+ (9.5 %) under inert conditions. Generating the imidazolium unit, yielding Ru(RR'ip)‐complexes lead to notable loss of quantum yields. Furthermore, we observed an enhanced photostability of Ru(RR'ip) complexes in the case of ortho substituted aryl groups. Abstract : Shine bright : The influence of several different aryl substituents at an imidazole unit on the structural, photophysical and photochemical properties of novel ruthenium polypyridyl‐based complexes is investigated. Further functionalization with a benzyl group leads to novel ruthenium complexes bearing an aryl and alkyl substituent on the imidazolium unit.